(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article analyzes the peculiarities of the development of coordination abilities of boxers in basic training groups in the training process. It has been established that in competitive activities, boxers need to effectively perform motor tasks that arise in the dynamic and unpredictable conditions of a fight. Solving such problems is directly related to the level of development of coordination abilities, which primarily determines the prospects for athletes’ further professional improvement. An analysis of scientific and methodological literature has shown that the structure of agility and coordination includes a set of independent types of coordination abilities that have specific features of manifestation in boxing. They can be differentiated by the nature of motor actions, the criteria for their assessment, and the factors that determine the level of development of these abilities. The effectiveness of technical and tactical actions in boxing, in particular punches, dodges, movements, and combination actions, largely depends on the athlete’s ability to coordinate the movements of the upper and lower limbs, maintain balance, orientate themselves in space, and react to the opponent’s actions in a timely manner. A high level of coordination training contributes to the economical use of energy resources, increased speed and strength indicators, accuracy of technical actions, and stability of competitive activity. It has been established that the level of development of boxers’ coordination abilities is determined by the complex interaction of psychophysiological functions: sensorimotor, proprioceptive, perceptual, and intellectual. The highest results in competitive activities are achieved by athletes who have developed sensory-perceptual abilities that ensure speed of reaction, accuracy of perception of an opponent’s movements, and optimal tactical decision-making. The main factors influencing the manifestation of coordination abilities in young boxers have been identified, and the feasibility of using special exercises aimed at developing balance, sense of rhythm, spatial orientation, and coordination of movements has been substantiated. It is proposed to test coordination indicators once every two months, which will allow the coach to monitor the dynamics of athletes’ preparedness and adjust the content of the training process in accordance with the results obtained. The criteria for assessing the level of development of coordination abilities are proposed to be the following indicators: speed, clarity, rationality, and ingenuity in performing motor actions, which have both qualitative and quantitative characteristics.